Multivariate data analysis - Hair, Joseph F (Prentice Hall, 2010)
"Multivariate Data Analysis is an applications-oriented introduction to multivariate analysis for the non-statistician. The seventh edition incorporates pivotal advances in technology that will assist students in gaining a firm understanding of statistical and managerial principles so as to develop a "comfort zone" not only for the statistical, but also the practical issues involved."--BOOK JACKET.